An Industrial Application of a Human-Robot Interface for People with Physical Disabilities Using Hand Gestures - Urrea-Onate, E (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper describes a 4DoF SCARA manipulator robot that is controlled by hand gestures using the SDK of the Kinect v2 sensor. A controller system is proposed that facilitates the inclusion of people with physical disabilities in industrial work environments. The entire system was evaluated in a specific sequence controller remotely by a person standing and sitting. The efficiency to complete the process in a low speed is 99% and at high speed is of 95%. © 2018 IEEE.